Respuesta :

The answer is c. If you plug in 1 where there are x's. The numerator is 0 making the whole equation equal to 0.

Answer:

C. 1

Step-by-step explanation:

We have the rational expression, [tex]\frac{(x-1)}{(x-3)(x+1)}[/tex].

After equating the expression to 0, we get,

[tex]\frac{(x-1)}{(x-3)(x+1)}=0[/tex]

i.e. [tex](x-1)=0\times [(x-3)(x+1)][/tex]

i.e. [tex](x-1)=0[/tex]

i.e. x= 1

Thus, the value for which the rational expression is equal to 0 is x= 1.

Hence, option C is correct.

ACCESS MORE